Contemporary Feminist Discourse, an Interdisciplinary Approach - Nowadays, feminist discourse requires an interdisciplinary approach, through the sociology or media studies. Comparing with other periods of time, the new feminists understood the inherent power of New Media and tend to use it as a tool, for making their (EIRP Proceedings, 2012)
Nowadays, feminist discourse requires an interdisciplinary approach, through the sociology ormedia studies. Comparing with other periods of time, the new feminists understood the inherent power ofNew Media and tend to use it as a tool, for making their message more popular. Is it effective? Is it a waste oftime? Although, it is premature to draw conclusions, the social facts that are to be used in this research (news,specific blogs and sites, feedback on social networks) seem to tilt the balance towards a positive impactcreated by recent feminist discourse. The aim of this research is to draw the features of the communicationestablished between feminist organizations, media institutions and media consumers, as it will be revealedduring the three case studies proposed. The pattern can be designed as follows: feminist organizations launcha message; media institutions ignore it or transform it into a piece of news; readers or listeners reach themessage, giving their immediate feedback on social networks, blogs and sites belonging to feministorganizations or media institutions. Feminist organizations are new comers in Romania, since the oldest ofthem being launched 10 years ago, comparing with European Women's Lobby, socially active for decades.Among the current Romanian feminist organizations Centrul Filia (Filia Center), Mame pentru Mame(Mothers for Mothers) and Pro Women will be analyzed. The novelty of this paper consists mostly inrevealing their online impact on Romanian audience.